An observational study of paternal body mass index and body composition during pregnancy. (16th November 2010) - Farah, N; Kelly, R; O'Connor, N; Kennelly, M; Stuart, B; Turner, MJ
Abstract : Maternal obesity has emerged as a major public health issue however, a paucity of information regarding Body Mass Index (BMI) and body composition specifically in fathers during pregnancy. This study aims to determine the BMI and the body composition of fathers-to-be and to compare the findings with the mother-to-be during pregnancy. The authors conducted a prospective observational study in a large university teaching hospital. The authors enrolled men whose partner booked for antenatal care in the first trimester of pregnancy. The height and weight of both parents-to-be were measured digitally and BMI calculated. The body composition of the couple was analysed using bioelectrical impedance. Of 167 fathers-to-be, 14% were obese (BMI >29.9 kg/m 2 ) compared with 16% of mothers-to-be (NS). However, 50% were overweight (BMI 25.0 – 29.9 kg/m 2 ) compared with 26% of mothers-to-be (p<0.001). The men had a lower overall fat percentage (p<0.001) but their visceral fat was higher than in the women (p<0.001). Our findings show a high level of obesity in fathers-to-be, which has implications not only for the men themselves but also their families. The authors suggest that public health obesity interventions may need to be family-centred.